Lead Poisoning Can Be Easily Misdiagnosed as Acute Porphyria and Nonspecific Abdominal Pain. (29th May 2017) - Tsai, Ming-Ta; Huang, Shi-Yu; Cheng, Shih-Yu
Abstract : Lead poisoning (LP) is less commonly encountered in emergency departments (ED). However, lead exposure still occurs, and new sources of poisoning have emerged. LP often goes unrecognized due to a low index of suspicion and nonspecific symptoms. We present a case of a 48-year-old man who had recurring abdominal pain with anemia that was misdiagnosed. His condition was initially diagnosed as nonspecific abdominal pain and acute porphyria. Acute porphyria-like symptoms with a positive urine porphyrin test result led to the misdiagnosis; testing for heme precursors in urine is the key to the differential diagnosis between LP and acute porphyria. The final definitive diagnosis of lead toxicity was confirmed based on high blood lead levels after detailed medical history taking. The lead poisoning was caused by traditional Chinese herbal pills. The abdominal pain disappeared after a course of chelating treatment. The triad for the diagnosis of lead poisoning should be a history of medicine intake, anemia with basophilic stippling, and recurrent abdominal pain.